Locally targeted cardiac gene delivery by aav microbubble destruction in a large animal model - Schlegel, Philipp; Huditz, Regina; Meinhardt, Eric; Rapti, Kleopatra; Geis, Nicolas; Most, Patrick; Katus, Hugo; Müller, Oliver J.; Bekeredjian, Raffi; Raake, Philip (Human gene therapy. Methods, 2016)
Cardiac gene therapy is a promising approach for treating heart diseases. Although clinical studies are ongoing, effective and targeted transgene delivery is still a major obstacle. We sought to improve and direct transgene expression in myocardium by ultrasound-targeted microbubble destruction (UTMD). In pigs, adeno-associated virus-derived (AAV) vectors harboring the luciferase reporter gene were delivered via retroinfusion into the anterior interventricular coronary vein (AIV). AAV vectors were either loaded to lipid microbubbles before injection or injected unmodified. Upon injection of AAV/microbubble solution, UTMD was performed. After 4 weeks, reporter gene expression levels in the anterior wall (target area), in the posterior wall (control area), and in noncardiac organs were analyzed. Retroinfusion of AAV-luciferase vectors loaded to lipid microbubbles led to a significant increase in transgene expression, with an increase in UTMD targeted areas of the anterior wall. Moreover, off-target expression was reduced in comparison to control animals, receiving AAV-luciferase without microbubbles. Besides an increase in overall target area transgene expression, UTMD alters the spatial expression of the luciferase transgene, focusing expression to ultrasound-targeted left ventricular wall. These data suggest UTMD as a promising approach for directing AAV to specific cardiac segments.